IMPLEMENTATION OF ISLAMIC GUIDANCE AND COUNSELING IN ADDRESSING ADOLESCENT ISSUES IN HIGH SCHOOLS - Muh. Nur Fithri D; Nurqadriani Nurqadriani; Sumarni Sumarni; Muhammad Nurhalim Hamzah L (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the implementation of Islamic Guidance and Counseling in addressing adolescent problems in secondary schools, focusing on the role of guidance and counseling (BK) teachers in fostering students’ Islamic character. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. The subjects consisted of BK teachers, school principals, and students at MA Muhammadiyah Salaka, Takalar Regency. The findings reveal that the Islamic guidance and counseling program is implemented through two main forms: Islamic guidance, emphasizing religious activities such as Qur’an learning and congregational prayers, and Islamic counseling, conducted in both group and individual settings. The program positively contributes to improving students’ moral awareness, discipline, and sense of responsibility. However, several challenges remain, including limited counseling facilities, the lack of professional counselors, and negative perceptions of BK services among students. The study concludes that the success of Islamic guidance and counseling depends largely on teachers’ exemplary conduct, school support, and parental involvement in character development. Therefore, it is recommended that schools enhance professional training for BK teachers, improve counseling facilities, and strengthen collaboration among schools, parents, and communities to create a conducive educational environment for nurturing students’ Islamic values and moral integrity.